Ecohydrological responses to solar radiation changes - Y. Wang; N. Meili; S. Fatichi (Hydrology and Earth System Sciences, 2025)
The implementation of future geoengineering projects to counteract global warming trends or more generally changes in aerosol loads alter solar radiation reaching the Earth's surface. These changes could have effects on ecohydrological systems with impacts which are still poorly quantified. Here, we compute how changes in solar radiation affect global and local near-surface meteorological variables by using CMIP6 model results. Using climate model outputs, we compute climate sensitivities to solar radiation alterations. These sensitivities are then applied to local observations and used to construct two sets of numerical experiments: the first focuses on solar radiation changes only, and the second systematically modifies precipitation, air temperature, specific humidity, and wind speed using the CMIP6-derived sensitivities to radiation changes, i.e., including its land–atmosphere feedback. We use those scenarios as input to a mechanistic ecohydrological model to quantify the local responses of the energy and water budgets as well as vegetation productivity spanning different biomes and climates.